Drug delivery by water-soluble organometallic cages - Therrien, Bruno (My University, 2012)
A review. Until recently, organometallic derivs. were generally viewed as moisture- and air-sensitive compds., and consequently very challenging to synthesize and very demanding in terms of lab. requirements (Schlenk techniques, dried solvent, glove box). However, an increasing no. of stable, water-sol. organometallic compds. are now available, and organometallic chem. in aq. phase is a flourishing area of research. As such, coordination-driven self-assemblies using organometallic building blocks are compatible with water, thus opening new perspectives in bio-organometallic chem. This chapter gives a short history of coordination-driven self-assembly, with a special attention to organometallic metalla-cycles, esp. those composed of half-sandwich complexes. These metalla-assemblies have been used as sensors, as anticancer agents, as well as drug carriers. [on SciFinder(R)]
Keywords: review organometallic cage drug delivery